River and city: microclimatic ameliorations and accretions of the ancient urban grain - Kamaruddin, Kamariah; Ibrahim, Illyani; Umi Kalsum, Nyimas (Palgrave Macmillan, 2023)
The river lies at the heart of the dynamic historical evolution of cities of maritime Southeast Asia, and the early growth of cities was primarily driven by the river—the “giver” of its life. Southeast Asian trade routes gave rise to water-based urban communities, and traders, visitors, and administrators settled and shaped cities around the growth of ports and river–estuary settlements. Cities grew initially into trading and administrative urban sites in edges and estuaries. Andaya (2008, p. 22) asserts in his observation of the link between historical geographies and the sociocultural nature of the archipelago: